Sport and school physical education in Medellín - González Palacio, E. V.; Padierna Cardona, J. C.; Córdoba Arboleda, M.; Escobar Barrera, J. M.; Gaviria García, N. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The present paper is part of the investigation. It aimed to identify and describe the status of sport and physical education in the town of Medellin from the assessments of teachers attending basic primary education in the town of Medellin, for which he used the quantitative approach from one study experimental descriptive, where 140 teachers from public and private educational institutions participated Medellin. Its main contributions are in the context of educational institutions and sports training, defining routes for improvement for both scenarios from complementary dimensions in policies, infrastructure, ongoing teacher training and discipline for professionals that serve the area and their extracurricular activities. It is striking that only 26.4% of teachers serving in primary area have specific training in Physical Education, Recreation and Sports, none of the participating teachers have doctoral degrees, only 26.4% of teachers Basic Elementary have exclusive Physical Education, Recreation and Sport dedication, among other findings. This entails a development path for the teaching and discipline of teachers of Physical Education, Recreation and Sports Primary Basic that must be addressed from the design of public policies, access to training posgradual levels, the establishment of teacher training programs discipline and permanent alliance from the Ministry of Education and the universities of the region in Antioquia and Colombia.